AVAILABILITY MODEL FOR A COGENERATION SYSTEM SUBJECTED TO REDUNDANCY - NASIR RESHID, MESERET (2013)
The main emphasis of cogeneration system is to provide electrical energy, steam, hot and chilled water to their customers. The failure of this system could lead to the disruption of the supply of these items. If failure occurs, it will result in reduction of availability as well as economic loss. In order to mitigate such effects, it is required to study availability of the cogeneration system together with associated economic loss. However, there are factors which affect the availability assessment of the cogeneration system. These factors are system redundancy and limitation of maintenance data. Use of redundancy in cogeneration helps to achieve higher availability but the operation cost of redundancy is expensive due to maximum demand charge cost.